Teacher Strategies in Developing 5 Aspects of Early Childhood Development in Darma Wanita Jenggala State Kindergarten - Eliyana, Eliyana; Ramzi, Muhajirin (JUPE : Jurnal Pendidikan Mandala, 2023)
This research aims to describe teachers' strategies in developing 5 aspects of development at the Darma Wanita Jenggala State Kindergarten. The method used in this research is a qualitative-descriptive method and approach. The techniques used in this research are interview techniques, observation and documentation. The research results show teacher strategies in developing 5 aspects of development, that teacher strategy is a very important component to be carried out by teachers in PAUD or Kindergarten level institutions, because whether or not a learning goal is achieved depends on the strategy used. Through PAUD and Kindergarten educational institutions, teachers are expected to be able to stimulate 5 aspects of good development Development of Religious and Moral Values, Physical-Motor Development, Cognitive Development, Language Development, and Social-Emotional Development, at the Darma Wanita Jenggala State Kindergarten, we always prioritize strategies to support learning and methods and media that are good and appropriate to support the learning process that is carried out and adapted to the themes that will be presented at each learning meeting.